Study on the Empowerment Status of Rural Stakeholders through Ornamental Birds Rearing in the State of West Bengal, India - Sukanta Biswas, (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2026)
Birds contribute significantly to the environment and to human well-being by aiding in pollination, dispersing seeds, regulating pest populations, helping in waste breakdown, and offering companionship. In West Bengal, keeping ornamental birds is becoming increasingly popular because it demands minimal investment, needs only a small area, and offers emotional satisfaction. This study explored the empowerment status of rural stakeholders through ornamental bird rearing by examining their socioeconomic, communication, and socio-psychological characteristics, knowledge, attitude, and adoption of scientific practices along with entrepreneurial development. A total of 120 respondents from Cooch Behar, Howrah, Hooghly, and South 24 Parganas districts were selected randomly and data were collected using a pre-tested interview schedule. Statistical analysis was conducted using frequency, percentage, mean, standard deviation, Kruskal–Wallis test, and correlation analysis with the Statistical Package for the Social Sciences 20.0 software. Findings indicated that the majority of participants were in their middle age, married and belonged to nuclear households. Income from ornamental bird rearing formed an important part of household earnings. Respondents mainly faced constrains, such as limited technical expertise, poor marketing infrastructure and minimal professional support. It was concluded that rural stakeholders could be empowered and socio-economic development promoted through proper training, technical guidance and market development in ornamental bird rearing.